ChemInform Abstract: Negative Thermal Expansion and Low‐Temperature Heat Capacity Anomalies of Ge31P15Se8 Semiclathrate. Issue 38 (September 2016) - Novikov, V. V.; Matovnikov, A. V.; Mitroshenkov, N. V.; Shevelkov, A. V.
Abstract: Polycrystalline Ge31 P15 Se8 samples are prepared by solid state reaction of stoichiometric amounts of Ge, red P, and Se (evacuated silica tubes, 874 K, 8 d).